Billing models for measuring nursing care in inpatient and outpatient settings: a scoping review - Marco Di Nitto; Francesca Napolitano; Michela Calzolari; Yari Longobucco; Vittorio Masotta; Francesco Zaghini; Rosaria Alvaro; Giancarlo Cicolini; Loreto Lancia; Duilio Fiorenzo Manara; Laura Rasero; Gennaro Rocco; et al. (BMC Health Services Research)
Abstract Background The rising cost of healthcare is a concerning issue for healthcare systems. The Diagnosis Related Group (DRG) system lacks direct consideration for costs related to nursing care. Therefore, to date there is no clear picture of billing models that consider also nursing activity when evaluating healthcare service costs or what factors related to nursing care affect the costs of healthcare services and would therefore need to be considered in billing models. Methods A scoping review was conducted. We searched articles published from January 2000 to September 2023, in English, Italian and Spanish. We consulted MEDLINE (Pubmed), CINAHL (EBSCOhost), Web of Science (Clarivate), SCOPUS (Elsevier), ProQuest and Google Scholar, government sites and major international bodies (e.g., National Health Service NHS, World Health Organization WHO). Results We included a total of 31 studies. The results highlighted 3 categories of factors related to nursing costs, which involve the organisation (e.g., nurse-to-patient ratio), nurses (e.g., skill mix, interventions), and patients (e.g., patient complexity, patient outcomes). All the billing models reported in the literature considered one or more of these categories to estimate nursing costs. The results also showed that appropriate management of organisational and nursing factors, such as staffing and skill mix, could improve healthcare service costs, nursing care or practice, and patient outcomes. Conclusions This study sheds light on the multifaceted aspects of nursing care that should be considered in a specific, comprehensive, billing model. Additional testing of existing models to verify their effectiveness, as well as the organisation of a permanent committee (or Task Force) that develops a comprehensive billing model, are necessary to guide the formulation of new policies.